2019
DOI: 10.1590/0102-7786344067
|View full text |Cite
|
Sign up to set email alerts
|

Condições Atmosféricas Associadas a Eventos de Ressaca no Litoral Sul e do Sudeste do Brasil durante o El Niño 2015/2016

Abstract: Resumo Os sistemas meteorológicos que ocasionam tempestades acompanhadas de ventos fortes, como frentes frias e ciclones extratropicais e subtropicais, muitas vezes interferem na condição de agitação do mar. Como consequência, o nível do mar pode se elevar extraordinariamente causando inundações na costa. Os anos de 2015 e 2016 foram caracterizados pela ocorrência da fase positiva do fenômeno El Niño - Oscilação Sul, com intensidade muito forte. O Sul do Brasil apresentou maiores condições de instabilidade atm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
(19 reference statements)
0
4
0
3
Order By: Relevance
“…The period of minimum wind speed occurs between March and May (autumn), with wind speed classes varies between 1.4–1.9 and 1.0–1.4 m·s −1 . This period of minima is directly associated with SASA, especially over coastal regions (Oliveira and Silva Quaresma, 2018; Machado et al ., 2019; Pantoja et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The period of minimum wind speed occurs between March and May (autumn), with wind speed classes varies between 1.4–1.9 and 1.0–1.4 m·s −1 . This period of minima is directly associated with SASA, especially over coastal regions (Oliveira and Silva Quaresma, 2018; Machado et al ., 2019; Pantoja et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Frontal systems (FS) also contribute to the occurrence of rainfall extremes and changes in the wind regime over SEB (de Morais et al ., 2010; Reboita et al ., 2010; Grimm, 2011; Andrade and Cavalcanti, 2018; Oliveira and Silva Quaresma, 2018; Sobral et al ., 2018b; Correia Filho et al ., 2021). In addition to the influence of SACZ and FS, the region's wind regime is strongly affected by the South Atlantic Subtropical Anticyclone (SASA) and by Atmospheric Blocking (AB) (Reboita et al ., 2010; Grimm, 2011; Gilliland and Keim, 2018b; Machado et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…LOSADA et al (2013) examined changes in sea level along with variations in tidal levels, storm surges and extreme events for different historical series and concluded that sea level is rising, storm surges are increasing, especially in the South, and El Niño events positively affect the sea level. The influence of El Niño in storm surges in more southern locations of the country was also pointed out by MACHADO et al (2019).…”
Section: Trends Of Slr In Brazilian Coastal Cities: An Overviewmentioning
confidence: 93%
“…Some populations of this species are known to tolerate fluctuations in the physical and chemical parameters of the water, maintaining stable populations between seasons (Freret‐Meurer, 2010), although the impact of El Niño events on these populations is still unclear. The 2015/2016 El Niño event was classified by the Golden Gate Weather Service as a strong anomaly, raising the ocean water surface by 2°C, and also causing atmospheric instability (Kayano et al ., 2019), intensifying extratropical storms and hangovers (Machado et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%